Factores que inciden en el desarrollo empresarial de las mypes del sector turismo en la ciudad de Yurimaguas, departamento de Loreto - Molina Pizango, Lizzi Celesthe (2023)
The thesis entitled: "Factors that affect the business development of MYPES in the tourism sector in the city of Yurimaguas, Department of Loreto", had the purpose of identifying the variables that determine the various indicators of Legislation, Microenterprise, Market and Technology and, of the Resources of the MYPES in the city carried out the study. The methodology was developed with a quantitative approach, of a cross-sectional type with a descriptive research design, a single sample was applied and it was made up of 26 micro and small lodging companies. The results address change results for companies to walk towards success, so it is necessary, the indicators that companies must change and work on are: Avoid fines and penalties by complying with tax payments. Know in depth the Promotion of Supply and demand. Search internal and external markets. Improve care with staff training. Workers must assume commitment to the company. The hypothesis has been demonstrated in which it is corroborated that "The greater the negative factor, the less business development of the MYPES of the tourism sector of the Yurimaguas city".